Transformasi Digital dalam Pelayanan Kenaikan Pangkat ASN: (Studi Kasus Implementasi SIPEKAT di Kabupaten Sidoarjo) - Ali Muhtadin; Amirul Mustofah; Eny Haryati (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2025)
Digital transformation in public services is an absolute necessity in the era of the Industrial Revolution 4.0, including in local government personnel management. This research analyses the digital transformation of civil servants’ (ASN) promotion services through the implementation of the Promotion Management System (SIPEKAT) at the Regional Personnel Agency of Sidoarjo Regency. Employing a qualitative approach with data collection techniques through in-depth interviews, participant observation, and documentation study, this research explores the transformation process from a manual to a digital system, the implementation challenges, and its impact on service effectiveness and efficiency. The results indicate that the digital transformation via SIPEKAT successfully increased processing time efficiency by up to 60%, reduced the use of physical documents by up to 85%, and improved the transparency and accountability of the services. However, challenges were found, including a digital competence gap among employees, limitations in technological infrastructure in several Regional Government Work Units, and resistance to change from some stakeholders. The novelty of this research lies in the comprehensive analysis of the digital transformation ecosystem of personnel services, integrating technological, organisational, and user behaviour perspectives, whilst producing an e-government implementation model for personnel services that can be adopted by other local.